2021
DOI: 10.1016/j.jpeds.2020.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Reply

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…The differences we observe in first-positive RT-PCR viral load between groups based on age are minor, as in other studies (31)(32)(33)(34)(35) and the viral loads in question, in the range of 5.9 to 6.6 (Table 1), are in a region of the viral load / culture probability association where changes in viral load have relatively little impact on estimated culture probability (Fig. 2C).…”
Section: Estimated Infectiousness In the Youngsupporting
confidence: 62%
“…The differences we observe in first-positive RT-PCR viral load between groups based on age are minor, as in other studies (31)(32)(33)(34)(35) and the viral loads in question, in the range of 5.9 to 6.6 (Table 1), are in a region of the viral load / culture probability association where changes in viral load have relatively little impact on estimated culture probability (Fig. 2C).…”
Section: Estimated Infectiousness In the Youngsupporting
confidence: 62%
“…They reported a correlation with sex that was not con rmed in our sample. Yonker et al [12] reported similar results in children, with those affected with the more severe forms of the disease presenting an increased humoral response.…”
Section: Discussionmentioning
confidence: 72%
“…Studies in SARS-CoV-2-infected patients are still scarce. Yonker et al [12] studied ACE2 expression in infected and healthy children, reporting increased expression in children older than 10 years and in those who had been infected by SARS-CoV-2. In our series, we found a different gradient of expression, with slightly increased expression of ACE2 in children < 18 years of age compared with adults, and increased expression in younger compared with older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jika dibandingkan dengan orang dewasa, virus yang terdeteksi pada tinja anak bertahan lebih lama (bisa mencapai 4 minggu). Maka, pengendalian pandemi ini harus lebih memperhatikan lagi kepada anak-anak (Yonker et al, 2020).…”
Section: Pendahuluanunclassified